THE PUBLIC MEZZANINE CAPITAL: FEASIBILITY STUDY - E. O. Stepanova (Финансы: теория и практика)
A growing number of financial institutions are unable to raise the required amount of equity and have to raise their own funds by means of public mezzanine. If these problems continue, the role of hybrids may become more significant, as they may be considered as a replacement of common equity for the purpose of counter-cyclical buffers, capital surcharges and so on. Thus, the importance of mezzanine capital for the financial system is already established and has a potential for further growth, while regulatory aspects and risk assessment of these relatively new instruments remain unsolved. In the article, the author analyses key regulatory concerns of Basel Accords in regards to mezzanine instruments, assesses the methodology of rating agencies to evaluate the risks incorporated in hybrid securities and compares the risk profiles of traditional convertible and recently developed contingent convertible bonds. The results articulate that measures applied by both Basel Committee members and rating agencies (Fitch, Moody’s, etc.) are not sufficient to manage risks incorporated in hybrid securities. The latter may contribute to the growth of financial failures we have observed in recent years.